Examining the Potentials and Limitations of Using Temperature Tracing to Infer Water Flux through Unsaturated Soils - Clutter, M. (2020)
This study used HYDRUS‐1D to simulate one‐dimensional vertical movement of water and heat. Temperature time series were analyzed for different materials, depths, and applied fluxes to understand the limitations of temperature methods for monitoring steady‐state water flux under unsaturated conditions. The conditions used in this analysis were intended to explore the minimum standards needed for unsaturated, steady‐state flux estimation. If these conditions cannot be met, then it is unnecessary to look at more challenging conditions (e.g., heterogeneity, transient flux, and unknown hydraulic and thermal properties). Previous work has suggested that there is a minimum flux that is measurable with temperature methods. The low saturated hydraulic conductivities of fine‐grained materials limit the applicability of temperature methods to high fluxes that lead to near‐saturated conditions for these materials. Although coarser soils have higher hydraulic conductivities, thermal diffusivity increases significantly with decreasing water content and may still complicate flux measurements for unsaturated conditions. As a result, we conclude that temperature‐based methods in unsaturated conditions will most likely fail even with the most simplifying assumptions for most soil types. Therefore temperature methods should be restricted to monitoring steady‐state fluxes in coarse soils and/or conditions near saturation.